Structural dynamics of P-type ATPase ion pumps. (11th October 2019) - Dyla, Mateusz; Basse Hansen, Sara; Nissen, Poul; Kjaergaard, Magnus
Abstract: P-type ATPases transport ions across biological membranes against concentration gradients and are essential for all cells. They use the energy from ATP hydrolysis to propel large intramolecular movements, which drive vectorial transport of ions. Tight coordination of the motions of the pump is required to couple the two spatially distant processes of ion binding and ATP hydrolysis. Here, we review our current understanding of the structural dynamics of P-type ATPases, focusing primarily on Ca 2+ pumps. We integrate different types of information that report on structural dynamics, primarily time-resolved fluorescence experiments including single-molecule Förster resonance energy transfer and molecular dynamics simulations, and interpret them in the framework provided by the numerous crystal structures of sarco/endoplasmic reticulum Ca 2+ -ATPase. We discuss the challenges in characterizing the dynamics of membrane pumps, and the likely impact of new technologies on the field.